Anthelmintic effect of betel nut (Areca catechu) and neem (Azadirachta indica) extract against liver fluke (Fasciola spp.) - Yamson, Elnalyn C; Tubalinal, Gabriel Alexis SP; Viloria, Victoria V; Mingala, Claro N (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study aimed to measure the anthelmintic effects of betel nut (Areca catechu) and neem (Azadirachta indica) leaf extracts against Fasciola spp. in vitro in comparison with the commercial dewormer, Albendazole, and the negative control, nutrient broth. The study determined the extract concentration that produced the highest efficacy based on the average recorded mean motility time, gross, and microscopic changes of the flukes treated with different concentrations of plant extracts. Material and Methods: The study consisted of eight treatments. Every treatment consisted of 10%, 20%, and 40% concentrations of both betel nut extract (BNE) and neem leaf extracts, positive control treatment (Albendazole-treated) and negative control treatment (25 ml nutrient broth). The motility of the flukes on all treatments was based on the established motility criteria scoring. The flukes subjected to all treatments were processed for histopathological analysis. Results: The result of the study revealed that after exposure of Fasciola spp. under 10%, 20%, and 40% extract concentrations, betel nut showed higher efficacy having the recorded mean motility time of 0.22, 0.07 min, and no movement upon contact, respectively, than Albendazole which produced mean motility time of 0.38 min. Nevertheless, the flukes treated with 10%, 20%, and 40% neem leaf extracts obtained the average mean motility time of 220, 151, and 98 min, respectively. Conclusions: The results gathered showed that 40% BNE concentration showed the highest efficacy based on the recorded mean motility time. All treatments of betel nut extract evidently showed marked changes in the gross and microscopic morphology of the flukes. However, the neem extract was ineffective in all concentrations although changes were observed microscopically. Furthermore, the nutrient broth was proven to be effective as a culture medium since the flukes remained active until 8 h of exposure. J. Adv. Vet. Anim. Res., 6(1): 44-49, March 2019